The effect of naturally fermented vegetable nitrites on the color of vacuum packaged fresh pork - Summerfield, John (Kansas State University, 2012)
The objective of this research was to evaluate the effect of natural nitrites on objective color of vacuum packaged fresh pork. Sections of longissimus dorsi muscle (approximately 18 cm) were injected with solutions containing 0, 3, 6, 9 or 12 ppm of natural nitrite. Sections were sliced into chops (2.54 cm) and individually vacuum packaged. Raw chop surface L*, a* and b* values were measured at 1, 5, 15 and 30 days post packaging. At 1, 15 and 30 days post packaging chops were cooked and surface L*, a* and b* values were measured. Hue and Chroma values were calculated for all color measurements. Linear and quadratic contrasts were evaluated on treatments for all measured and calculated color values. A linear (P<0.05) increase was detected on the L* values for days of vacuum storage treatment, all other raw color measurements and calculations for levels of natural nitrite and days of vacuum package storage were found to be quadratic (P<0.05). Cooked L* and Hue values for days of vacuum storage were found to decrease linearly (P<0.05), all other days of storage and levels of nitrite treatments were found to be quadratic (P<0.05) in relationship to the measured and calculated cooked color values. All raw chops containing nitrite had higher a* and Chroma values at all evaluation days than those containing no added nitrite. Raw chops containing nitrite had lower L*, higher b* and Hue values than the 0 ppm chops (P<0.05). Raw chops containing natural nitrite were darker, redder, more yellow and more intense in color than those without nitrite. The longer the chops were vacuum packaged and then cooked, the lower the L* values were (P<0.05). Cooked chops containing nitrite were redder, less yellow and lower in Hue and Chroma values than cooked chops with no added nitrite P(<0.05). These results indicate that low levels of nitrite can alter fresh and cooked pork color during vacuum storage. To balance the increased redness and darkness of the raw chops with the increased redness of the cooked chops, 3 ppm of natural nitrite was found to be the optimal treatment.
Keywords: Color; Natural nitrite; Pork; Vacuum package; Food Science (0359)